Urban Sociable Streetscape: A Review of Jalan Raja Alang, Kampung Baru, Kuala Lumpur - Rosnan, Muhamad Adli Faezal; Awaluddin, Zuraina Leily; Aminuddin, A M R; Shukri, Sharyzee Mohmad (MAJ - Malaysia Architectural Journal, 2021)
This research concerns the visual connection of nodes between environment and community in an urban street of Kuala Lumpur, Jalan Raja Alang, Kampung Baru. This street act as a secondary road in Kampung Baru where it connects both primary roads, Jalan Tunku Abdul Rahman and Jalan Raja Abdullah. With the advantages of the existing Food Paradise concept, this street might become a great need for a third place, a sociable streetscape. This research objective is to enliven Jalan Raja Alang as the new social node for the community in improving their wellbeing and livelihoods. The advent of sociable streetscape was motivated by the lack of security for walking activities in the area. Majority of the local were threaten by the road hazards and polluted surroundings. Hence, the respondents were asked to describe the street in accordance with the efficacy of the current streetscape and to suggest several recommendations for better refinement of the street. The results shows that the existing streetscape can be improved and possible to become an urban sociable streetscape in the city. In addition, majority of the respondents also agreed with the aim and the objective proposed